Discovery of new antimicrobial thiophene derivatives with activity against drug-resistant Gram negative-bacteria - Molina-Panadero, Irene; Morales-Tenorio, Marcos; García-Rubia, Alfonso; Ginex, Tiziana; Eskandari, Khalil; Martinez, Ana; Gil, Carmen; Smani, Younes (Frontiers in Pharmacology, 2024)
Our aim is to identify new small molecules with antimicrobial potential, especially against colistin-resistant (Col-R) Acinetobacter baumannii and Escherichia coli. After initial hits identification by fingerprint similarity, MIC of 24 heterocyclic derivatives for A. baumannii and E. coli reference strains, and bactericidal activity of selected thiophenes against Col-R strains were determined. We analyzed changes in bacterial membrane permeability and the OMPs profile. Additionally, we determined bacterial adherence to host cells and performed molecular docking studies to assess their binding to bacterial targets. The compounds' MICs ranged from 4 to >64mg/L. Thiophene derivatives 4, 5 and 8 exhibited MIC50 values between 16 and 32mg/L for Col-R A. baumannii and 8 and 32mg/L for Col-R E. coli. The time-kill curve assay demonstrated that thiophenes 4 and 8 had bactericidal effects against Col-R A. baumannii and E. coli. Furthermore, treatment with them resulted in increased membrane permeabilization and reduced adherence of these isolates to host cells. Finally, the docking studies showed a stronger binding affinity to CarO1 and Omp33 of A. baumannii and OmpW and OmpC of E. coli. These findings indicate that thiophene derivatives possess antibacterial activity against Col-R A. baumannii and E. coli, suggesting that they may enhance the repertoire of drug treatments against bacteria.